2012
DOI: 10.1007/s10875-012-9797-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplantation B Cell Function in Different Molecular Types of SCID

Abstract: Purpose Severe combined immunodeficiency (SCID) is a syndrome of diverse genetic cause characterized by profound deficiencies of T, B and sometimes NK cell function. Non-ablative HLA-identical or rigorously T cell-depleted haploidentical parental bone marrow transplantation (BMT) results in thymus-dependent genetically donor T cell development in the recipients, leading to a high rate of long-term survival. However, the development of B cell function has been more problematic. We report here results of analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 54 publications
(60 reference statements)
2
72
0
Order By: Relevance
“…Following GT, all patients reported infection AEs, including severe, opportunistic, and urinary tract infections. Infections of the respiratory and gastrointestinal tracts were the most frequently reported AEs; these organ systems are targets for infections in both ADA-SCID 42 and normal pediatric populations. 36 Following GT, the majority of infectious AEs were not serious, and all infectious AEs resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Following GT, all patients reported infection AEs, including severe, opportunistic, and urinary tract infections. Infections of the respiratory and gastrointestinal tracts were the most frequently reported AEs; these organ systems are targets for infections in both ADA-SCID 42 and normal pediatric populations. 36 Following GT, the majority of infectious AEs were not serious, and all infectious AEs resolved.…”
Section: Discussionmentioning
confidence: 99%
“…11 One study suggested that donor B-lymphocyte chimerism is required for establishment of functioning B lymphocytes in IL2RG, JAK3, and VDJ-recombinant defect SCID genotypes. 12 Sustained thymopoiesis and donor Blymphocyte chimerism may require administration of myeloablative preparative regimens 7,13,14 and modified T-lymphocyte depletion techniques. 15 Long-term immune function may impact on subsequent health-related quality of life (QoL) and presence or absence of ongoing medical issues, which may be dependent on prior use of a preparative regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, poor B cell reconstitution defined by continued need for IVIG replacement is common (15% to 58%) on long-term follow-up 11,13,23 . Patients with IL7Rα, CD3, and ADA SCID are more likely to recover B cell immunity, as host B cells may function normally with competent donor T-cell help 23 . Conversely, IL2RG and JAK3 SCID patients have intrinsically dysfunctional B cells and require donor B cell engraftment for normal B cell function post-HCT 23 .…”
Section: Immune Reconstitutionmentioning
confidence: 99%
“…Patients with IL7Rα, CD3, and ADA SCID are more likely to recover B cell immunity, as host B cells may function normally with competent donor T-cell help 23 . Conversely, IL2RG and JAK3 SCID patients have intrinsically dysfunctional B cells and require donor B cell engraftment for normal B cell function post-HCT 23 . The use of either myeloablative or reducedintensity conditioning, particularly busulfan-containing regimens, is associated with improved ability to achieve B cell engraftment and immunoglobulin independence in all forms of SCID.…”
Section: Immune Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation